2023
DOI: 10.3390/ijms242316633
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Sphingolipid Catabolism Enzymes along the Nephron: Novel Early Urinary Biomarkers of Renal Damage

Martha Franco,
Agustina Cano-Martínez,
María del Pilar Ramos-Godínez
et al.

Abstract: The objective of this study was to investigate whether the activity of enzymes involved in sphingolipid catabolism could be biomarkers to predict early renal damage in streptozotocin (STZ)-induced diabetic rats and Angiotensin II (Ang II)-induced hypertension rats. Diabetic and hypertensive rats had no changes in plasma creatinine concentration. However, transmission electron microscopy (TEM) analysis showed slight ultrastructural changes in the glomeruli and tubular epithelial cells from diabetic and hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A series of elegant basic studies recently suggested that sphingolipids are promising urinary biomarkers for kidney diseases ( 1 , 2 ). The sphingolipids are composed of a hydrophobic and a hydrophilic chain, with the various fatty acid components of each sphingolipid determining its species ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A series of elegant basic studies recently suggested that sphingolipids are promising urinary biomarkers for kidney diseases ( 1 , 2 ). The sphingolipids are composed of a hydrophobic and a hydrophilic chain, with the various fatty acid components of each sphingolipid determining its species ( 3 ).…”
Section: Introductionmentioning
confidence: 99%